Mapping health behaviour related to Chagas diagnosis in a non-endemic country: Application of Andersen’s Behavioural Model - Iglesias-Rus, Laura; Romay-Barja, María; Boquete, Teresa; Benito, Agustín; Jordan, Briggitte; Blasco-Hernández, Teresa (PloS one, 2022)
Chagas disease has become a challenge for non-endemic countries since population mobility has increased in recent years and it has spread to these regions. In order to prevent vertical transmission and improve the prognosis of the disease, it is important to make an early diagnosis. And to develop strategies that improve access to diagnosis, it is important to know the factors that most influence the decision of the population to know their serological status. For this reason, this study uses Andersen's Behavioural Model and its proposed strategies to explore the health behaviours of Bolivian population. Twenty-three interviews, two focus groups, and two triangular groups were performed with Bolivian men and women, involving a total of 39 participants. In addition, four interviews were conducted with key informants in contact with Bolivian population to delve into possible strategies to improve the Chagas diagnosis. The most relevant facts for the decision to being diagnosed pointed out by participants were having relatives who were sick or deceased from Chagas disease or, for men, having their pregnant wife with a positive result. After living in Spain more than ten years, population at risk no longer feels identified with their former rural origin and the vector. Moreover, their knowledge and awareness about diagnosis and treatment still remains low, especially in younger people. Limitations on access to healthcare professionals and services were also mentioned, and proposed strategies focused on eliminating these barriers and educating the population in preventive behaviours. Based on Andersen's Behavioural Model, the results obtained regarding the factors that most influence the decision to carry out Chagas diagnosis provide information that could help to develop strategies to improve access to health services and modify health behaviours related to Chagas screening.